VO#042 Quotation for additional components in plumbing works rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of price quotation for additional components in plumbing works of BRACU new campus project.